Analisis Pengaruh Jumlah Tenaga Kerja Terhadap Financial Performance dengan Metode Analisis Regresi dan Korelasi di PT Migas - Riyadi, Attila Daffa; Tranggono (Jurnal Serambi Engineering, 2025)
Labour serves as a critical resource that has a significant impact on a company's operations and financial results, particularly in the oil and gas sector, which contributes to national economic development. This research focuses on evaluating the impact of workforce size on the financial performance of PT Migas using regression and correlation analysis techniques. The study uses financial ratios such as return on assets (ROA), return on equity (ROE), earnings before interest, tax, depreciation and amortisation (EBITDA) and operating costs as data variables. The results show a weak inverse relationship between the number of employees and ROA, with a correlation coefficient of -0.526, indicating a negative association. Similarly, the correlation between the number of employees and ROE is calculated at -0.332, while the correlations with operating expenses and EBITDA are -0.991 and -0.848 respectively, all indicating a negative trend. Over the three-year analysis period, the results show that the size of the workforce does not have a significant impact on financial performance. This highlights the potential influence of other factors on firm performance and the need for management to implement more efficient workforce strategies. This study aims to provide valuable quantitative insights for management in formulating labour-related policies to support the company's future financial growth.